Self‐Referencing and Persuasion: Narrative Transportation versus Analytical Elaboration - Escalas, Jennifer Edson (Journal of Consumer Research, 2007)
This article contrasts narrative self-referencing with analytical self-referencing. I propose that narrative self-referencing persuades through transportation, where people become absorbed in a story—in this case, in their storylike thoughts (Green and Brock 2000). When ad viewers are transported by these narrative thoughts, persuasion is not negatively affected by weak ad arguments. Conversely, analytical self-referencing persuades via more traditional processing models, wherein cognitive elaboration is enhanced by relating incoming information to one’s self or personal experiences, which results in a differential persuasive effect of strong versus weak arguments. I also propose that ad skepticism moderates the effect of narrative transportation. My assertions are tested in two experiments in the context of mental simulation as a form of narrative self-referencing. Self-referencing occurs when one processes information by relating it to one’s self or personal experiences (Burnkrant and Unnava 1995). Some consumer research has found that self-referencing serves to increase product feature